2009
DOI: 10.1002/pen.21327
|View full text |Cite
|
Sign up to set email alerts
|

Nylon 66/clay nanocomposite structure development in a twin screw extruder

Abstract: Nylon 66/clay nanocomposites were prepared in a Berstorff ZE25A UTX Ultra-glide corotating twin screw extruder at 2708C. Two types of extruder configurations with different mixing sections were used. One comprised two kneading block sections in the screws (KB only) and the other had a combination of a multiprocess-element (MPE) section and a kneading block section. Samples at eight different locations along the extruder screw were obtained and analyzed using scanning electron microscope and transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
1
14
0
2
Order By: Relevance
“…The wear behavior of a polymer in dry sliding condition is strongly influenced by its ability to form a transfer film on the counterface [30, 31]. The transfer films provide a shielding of the soft polymer surface from the hard metal asperities [15, 16, 32–35]. This study revealed that anti‐wear properties of PA 66/CB composites are improved markedly after incorporation of MoS 2 .…”
Section: Resultsmentioning
confidence: 92%
“…The wear behavior of a polymer in dry sliding condition is strongly influenced by its ability to form a transfer film on the counterface [30, 31]. The transfer films provide a shielding of the soft polymer surface from the hard metal asperities [15, 16, 32–35]. This study revealed that anti‐wear properties of PA 66/CB composites are improved markedly after incorporation of MoS 2 .…”
Section: Resultsmentioning
confidence: 92%
“…It was obvious that the pure PA66 in Figure 8(a) displayed only one melting peak and the PA66/rGO nanocomposites exhibited two melting peaks. According to the report of Lin et al [34], the pure PA66 showed only one melting temperature (T mI ) at around 260°C, which is the temperature found for Form I or the α-type peak [35]. The second melting temperature (T mII ) detected was at around 252°C which was attributed to Form II or the γ-type peak.…”
Section: Characterizations and Properties Of Pa66/rgomentioning
confidence: 91%
“…9B shows two peaks. The first sharp peak at 253 • C is due to melting [32]. The 2nd broad peak around 450 • C is obviously due to decomposition of nylon.…”
Section: The Comparison Of MCC and Dsc For The Study Of The Fr Cottonmentioning
confidence: 96%